Is Bone Loss or Devascularization Associated With Recurrence of Osteomyelitis in Wartime Open Tibia Fractures?. Issue 4 (April 2019) - Petfield, Joseph L.; Tribble, David R.; Potter, Benjamin K.; Lewandowski, Louis R.; Weintrob, Amy C.; Krauss, Margot; Murray, Clinton K.; Stinner, Daniel J.
Abstract: Background: During recent wars, 26% of combat casualties experienced open fractures and these injuries frequently are complicated by infections, including osteomyelitis. Risk factors for the development of osteomyelitis with combat-related open tibia fractures have been examined, but less information is known about recurrence of this infection, which may result in additional hospitalizations and surgical procedures. Questions/purposes: (1) What is the risk of osteomyelitis recurrence after wartime open tibia fractures and how does the microbiology compare with initial infections? (2) What factors are associated with osteomyelitis recurrence among patients with open tibia fractures? (3) What clinical characteristics and management approaches are associated with definite/probable osteomyelitis as opposed to possible osteomyelitis and what was the microbiology of these infections? Methods: A survey of US military personnel injured during deployment between March 2003 and December 2009 identified 215 patients with open tibia fractures, of whom 130 patients developed osteomyelitis and were examined in a retrospective analysis. No patients with bilateral osteomyelitis were included. Twenty-five patients meeting osteomyelitis diagnostic criteria were classified as definite/probable (positive bone culture, direct evidence of infection, or symptoms with culture and/or radiographic evidence) and 105 were classified as possible (bone contamination, organism growth in deep wound tissue, and evidence of local/systemic inflammation). Patients diagnosed with osteomyelitis were treated with débridement and irrigation as well as intravenous antibiotics. Fixation hardware was retained until fracture union, when possible. Osteomyelitis recurrence was defined as a subsequent osteomyelitis diagnosis at the original site ≥ 30 days after completion of initial treatment. This followup period was chosen based on the definition of recurrence so as to include as many patients as possible for analysis. Factors associated with osteomyelitis recurrence were assessed using univariate analysis in a subset of the population with ≥ 30 days of followup. Patients who had an amputation at or proximal to the knee after the initial osteomyelitis were not included in the recurrence assessment. Results: Of 112 patients meeting the criteria for assessment of recurrence, 31 (28%) developed an osteomyelitis recurrence, of whom seven of 25 (28%) had definite/probable and 24 of 87 (28%) had possible classifications for their initial osteomyelitis diagnosis. Risk of osteomyelitis recurrence was associated with missing or devascularized bone (recurrence, 14 of 31 [47%]; nonrecurrence, 22 of 81 [28%]; hazard ratio [HR], 3.94; 1.12–13.81; p = 0.032) and receipt of antibiotics for 22-56 days (recurrence, 20 of 31 [65%]; nonrecurrence: 37 of 81 [46%]; HR, 2.81; 1.05–7.49; p = 0.039). Compared with possible osteomyelitis, definite/probable osteomyelitis was associated with localized swelling at the bone site (13 of 25 [52%] versus 28 of 105 [27%]; risk ratio [RR], 1.95 [1.19-3.19]; p = 0.008) and less extensive skin and soft tissue injury at the time of trauma (9 of 22 [41%; three definite/probably patients missing data] versus 13 of 104 [13%; one possible patient missing data]; RR, 3.27 [1.60-6.69]; p = 0.001). Most osteomyelitis infections were polymicrobial (14 of 23 [61%; two patients with missing data] for definite/probable patients and 62 of 105 [59%] for possible patients; RR, 1.03 [0.72-1.48]; p = 0.870). More of the definite/probable patients received vancomycin (64%) compared with the possible patients (41%; p = 0.046), and the duration of polymyxin use was longer (median, 38 days versus 16 days, p = 0.018). Time to definitive fracture fixation was not different between the groups. Conclusions: Recurrent osteomyelitis after open tibia fractures is common. In a univariate model, patients with an intermediate amount of bone loss and those treated with antibiotics for 22 to 56 days were more likely to experience osteomyelitis recurrence. Because only univariate analysis was possible, these findings should be considered preliminary. Osteomyelitis recurrence rates were similar, regardless of initial osteomyelitis classification, indicating that diagnoses of possible osteomyelitis should be treated aggressively. Level of Evidence: Level III, therapeutic study.